Biomechanical Study on the Constructs of Bone Cement Incorporate with Screw for Anterior Spinal Stabilization: Comparison between the construct versus normal spine - TEJAPONGVORACHAl, Tawechai; PRASONGCHIN, Pairat; KUPTANIRATSAIKUL, Somsak; ITIRAVIVONG, Pibul; LEONG, John C. Y. (Journal of Metals, Materials and Minerals, 2022)
-